Reorganization of intruder Using Ad-Hoc Network And RFID - Vishakha Hagawane; Anukriti Anup Shrivastav; Kartiki Tambekar (IAES International Journal of Robotics and Automation (IJRA), 2014)
This system is to develop a centralized computer application that needs to identify moving person in a specific area using wireless network. In this paper, we develop a new indoor tracking algorithm using received signal strength. The RFID is able to detect the humans and provide information about the direction of the movement. The gathered information from the node is to be given to the base station for processing. . This application is able to detect and track person, and report direction of the intruder to a central base station. In this system we design nodes through which we are able to track the person. The human intruder is detected using Zigbee.